Unpacking sustainability practices of Western Cape wine supply chains: a practice-based view - Riley, Catarina Moura (2023)
Although sustainable supply chain management (SSCM) has become an important field for several industries, little is known in the wine industry. To fill this gap, this master thesis investigates intra- and inter-organizational sustainability practices implemented in Western Cape wine supply chains. In doing so, the practice-based view theory is used to understand why, how, and by whom these practices were implemented. South Africa was chosen because it has a robust wine sustainability scheme that includes 95% of the country’s grape growers and wine cellars. Nine case studies were conducted from May to September 2022 through semistructured interviews with managers from nine wineries and one cork supplier subsidiary located in Western Cape. A total of 12 interviews were carried out with an average duration of 90 minutes and transcribed for analysis. Observations were made in short vineyard and cellar tours. The data were analyzed within and cross-case. Data coding was performed with all transcribed interviews and to assist in this analysis, the author used a structured technique supported by ATLAS TI. All analyzed wineries have a vertical supply chain; they are responsible for all production stages, from growing grapes to bottling wine. 15 sustainability practices were identified. Most of these practices are both intra- and inter-organizational. Many practices are related to the environmental dimension of sustainability, e.g., managing soil sustainably, decreasing GHG emissions, and protecting local biodiversity. This is due to the fact that the region of Western Cape is prone to draught and fires, as well as biodiversity degradation. Also, all nine cases are part of the Integrated Production of Wine (IPW) scheme which audits the wineries on environmental criteria regularly. Besides that, the author identified practices that are more related to the social and economic dimensions of sustainability, such as assisting workers, developing and having an educational role in the community, and guaranteeing business continuity in times of crisis. These practices emerged due to South Africa’s context; the local government’s insufficient health assistance and educational opportunities to underprivileged populations, alcohol sale restrictions during COVID-19 lockdowns, and the national electricity crisis that imposes long periods of loadshedding on the whole country. The practices are led by wine company owners, and managers, who usually have a personal tie to the surrounding environment, are motivated to solve environmental and social problems, and are responsible for ensuring sustainability certification for their business. A number of other individuals and organizations, such as NGOs, conservancy groups, recycling companies, and suppliers are fundamental for interorganizational sustainability practices to take place. Moreover, financial, physical, natural, and human resources are necessary to implement sustainability practices along the wine supply chain. By showing intra- and inter-organizational sustainability practices, this master thesis reveals the necessary activities and resources needed to adopt these practices, and investigates how these practices emerged. In addition, managers in wine supply chains and other food and beverage industries could employ the identified practices in their respective companies, and thus address the United Nations Sustainable Developments Goals, such as, protecting life on land, climate action, quality education, and promoting good health and well-being.